2021
DOI: 10.1177/23779608211054817
|View full text |Cite
|
Sign up to set email alerts
|

Postgraduate Students’ Experience of Using a Learning Management System to Support Their Learning: A Qualitative Descriptive Study

Abstract: Introduction Educational institutions worldwide have implemented learning management systems (LMSs) to centralise and manage learning resources, educational services, learning activities and institutional information. LMS has mainly been used by teachers as storage and transfer of course material. To effectively utilise digital technologies in education, there is a need for more knowledge of student experiences with digital technology, such as LMSs and especially regarding how LMSs can contribute to student en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…23,24,37 Finally, repeated study of the content contributes to optimal exam preparation. 40 These key features have been shown to enhance learning effectiveness. 41 Regarding the limitations of this study, the generalisability of our results may be limited as we only examined data from one university with a relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…23,24,37 Finally, repeated study of the content contributes to optimal exam preparation. 40 These key features have been shown to enhance learning effectiveness. 41 Regarding the limitations of this study, the generalisability of our results may be limited as we only examined data from one university with a relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…For the students, on the other hand, it allowed remote learning with flexibility in time and place at their comfort 23,24,37 . Finally, repeated study of the content contributes to optimal exam preparation 40 . These key features have been shown to enhance learning effectiveness 41 …”
Section: Discussionmentioning
confidence: 99%
“…As the postgraduate students are geographically dispersed and mostly are working adults, it will be difficult to gather data from multiple postgraduate programs at large. We choose the postgraduate students because research have found they have different views regarding their own responsibility for using the LMS to prepare before on-campus activities (Steindal et al 2021).…”
Section: Methodsmentioning
confidence: 99%
“…It enables students to learn at any time and from any location. Steindal et al (2021) mentioned that during the onslaught of the pandemic covid-19, educational institutions worldwide have begun implementing learning management systems (LMSs) to centralize and manage learning resources, educational services, learning activities, and institutional information. This paper aims to enhance the E-Learning System through LMS Technologies in reshaping their learner experience.…”
Section: Introductionmentioning
confidence: 99%